2015
DOI: 10.1186/s12906-015-0666-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcendental Meditation for the improvement of health and wellbeing in community-dwelling dementia caregivers [TRANSCENDENT]: a randomised wait-list controlled trial

Abstract: BackgroundDementia is a prevalent neurodegenerative disorder affecting an estimated 24.3 million people across the globe. The burden on those caring for people with dementia is substantial, with widespread implications for the caregiver, the care recipient and the community. Relaxation techniques, such as Transcendental Meditation® (TM), have been shown to reduce stress and anxiety in healthy workers; similar benefits are anticipated in dementia caregivers. The objective of this study was to ascertain whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 35 publications
(40 reference statements)
0
65
1
Order By: Relevance
“…This can be due to that mental health promotion is dependent on health literacy rather than education level. However, this finding is in contrast to the results of Leach et al (6). Marital status was another irrelevant factor found in this study, while Andren and Elmstahl considered married caregivers to have more social support networks, resulting in less stress and better mental health (20).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This can be due to that mental health promotion is dependent on health literacy rather than education level. However, this finding is in contrast to the results of Leach et al (6). Marital status was another irrelevant factor found in this study, while Andren and Elmstahl considered married caregivers to have more social support networks, resulting in less stress and better mental health (20).…”
Section: Discussioncontrasting
confidence: 99%
“…caregivers' physical and psychological health (1). Other research has found that the employment of resilience training offers many advantages (5)(6)(7). Many resilience studies explore personal characteristics that may affect coping or resilience and focus on individuals experiencing specific adverse circumstances (e.g., illness, bereavement, abuse, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Of the few trials of non-KK mantra meditation [189, 190], mindfulness meditation [191195] and other meditation practices [196] in older adults that have assessed cognitive function, most have shown minimal or no improvement [190195], including two recent large RCTs of MBSR in generally healthy elders [191, 193]. To date, only two published trials of non-KK meditation have included adults with memory complaints, and only one specifically targeted this population.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, observed effects on neuropsychiatric impairment and QOL in older adults, including those with memory loss, have tended to be modest, with several studies showing limited or no improvement with either insight meditation [191194] or TM [190]. In contrast, preliminary trials to date of KK meditation in dementia caregivers [153, 197] and adults with early memory loss [94] have shown improvements in both cognitive function and psychosocial status consistent with those observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The 35 papers included a total of 3501 participants (Table 1), both caregivers and care recipients with a cognitive disorder. The papers described studies carried out in Asia [17,32,34], Europe [18,23,26,28,37,38,40,41,48], North America [16,[19][20][21][22]24,25,27,[29][30][31]35,36,39,[42][43][44][45][46][47] and Australia [14,15,33]. In 28 studies, data were collected in the homes of the participants using a face-to-face or in-person approach, telephone sessions or both.…”
Section: Resultsmentioning
confidence: 99%